Remarks by the delegate of the surgery society Dr. F. Etchegorry - Etchegorry, F. (Cirugía del Uruguay, 2020)
Session of August 12th, 1938. Remarks by the delegate of the surgery society Dr. F. Etchegorry to the disappearance of Juan Cunha.